A human rights-based approach to community justice: Adding value to desistance focused practice. (August 2017) - Cross, David
The article explores what is meant by a human rights-based approach to supervision and how such an approach can converge with desistance focused practice in order to impact on its effectiveness. Placing the discussion in the wider context of human rights developments in social services and of desistance focused approaches to effective supervision in the community, I explore the extent to which a human rights approach can add legitimacy to a desistance approach, identifying common themes between the approaches that would support this case. My findings support the contention that a human rights-based approach to supervision can add value to practice that supports desistance from crime.